2022
DOI: 10.3390/app12157383
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Neural Network PID Strategy Based on PSO Optimization for pH Control of Water and Fertilizer Integration

Abstract: In the process of crop cultivation, the application of a fertilizer solution with appropriate pH value is more conducive to the absorption of nutrients by crops. If the pH of the irrigation water and fertilizer solution is too high, it will not only be detrimental to the absorption of nutrients by the crop, but will also damage the structure of the soil. Therefore, the precise regulation of pH in water and fertilizer solutions is very important for agricultural production and saving water and fertilizer. First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In the actual fertilization process, the fertilizer mother liquor and irrigation water are added to the mixing tank first, and the pH value measured at this time is alkaline, then the acid tank solenoid valve is opened, and the pH value in the mixing tank is made to meet the requirements for cotton growth by controlling the opening time of the acid tank solenoid valve. An extensive literature review revealed that the most suitable pH values for cotton growth are between 6 and 7 [13].The process of mixing mother liquor, acid and irrigation water can be regarded as the process of acid-base neutralization [12].This process can consist of a dynamic equation describing the state variables and a static pH equation describing the neutralization titration. Assume that the volume V of the liquid before and after mixing in the mixing tank remains the same, and the mother liquor, water and acid are mixed uniformly.…”
Section: Description Of Water and Fertilizer Ph Adjustment Process An...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the actual fertilization process, the fertilizer mother liquor and irrigation water are added to the mixing tank first, and the pH value measured at this time is alkaline, then the acid tank solenoid valve is opened, and the pH value in the mixing tank is made to meet the requirements for cotton growth by controlling the opening time of the acid tank solenoid valve. An extensive literature review revealed that the most suitable pH values for cotton growth are between 6 and 7 [13].The process of mixing mother liquor, acid and irrigation water can be regarded as the process of acid-base neutralization [12].This process can consist of a dynamic equation describing the state variables and a static pH equation describing the neutralization titration. Assume that the volume V of the liquid before and after mixing in the mixing tank remains the same, and the mother liquor, water and acid are mixed uniformly.…”
Section: Description Of Water and Fertilizer Ph Adjustment Process An...mentioning
confidence: 99%
“…Considering the characteristics of the fertilizer pH control system, the mathematical model of the system needs to be obtained. According to the fertilizer application characteristics and the complexity of the system, this paper selects the first-order inertia plus delay link transfer function to describe the mathematical model of the fertilizer application control system [13].The model equation is as follows:…”
Section: System Model Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the pH of the fermentation material is lower than 5.5, methane production during the fermentation process will be inhibited, leading to a decrease in biogas production. Therefore, in order to increase the biogas production of dry straw fermentation material, it is necessary to control the pH of the material and establish a rapidly adjustable environmental pH control system [4,5], which is of great significance for improving fermentation efficiency and success rates.…”
Section: Introductionmentioning
confidence: 99%